1997
DOI: 10.1200/jco.1997.15.2.750
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of docetaxel and cisplatin in previously untreated patients with advanced non-small-cell lung cancer.

Abstract: Docetaxel 75 mg/m2 over 1 hour followed by cisplatin 75 mg/m2 over 1 hour is recommended for phase II studies. The responses seen in this phase I study suggest a high degree of activity of this combination in previously untreated advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Subsequent studies, however, consistently raised concerns about toxicity, notably neutropenia. 1,20,21 Preclinical studies have demonstrated that docetaxel modulates the intracellular metabolism of other drugs (5-FU and cisplatin), which explains the mechanism underlying the synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies, however, consistently raised concerns about toxicity, notably neutropenia. 1,20,21 Preclinical studies have demonstrated that docetaxel modulates the intracellular metabolism of other drugs (5-FU and cisplatin), which explains the mechanism underlying the synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 One study recommended a combination of docetaxel 75 mg/m 2 given over a 1-h period, followed by cisplatin 75 mg/m 2 , given over a 1-h period. 19 The other recommended two alternative combinations of these drugs, i.e., a combination of 1-h infusion of docetaxel, 100 mg/m 2 , followed by 3-h infusion of cisplatin, 75 mg/m 2 ; or docetaxel, 85 mg/m 2 , followed by cisplatin, 100 mg/m 2 . 20 Neutropenia was the predominant toxicity in these studies and in our own.…”
Section: Pk Resultsmentioning
confidence: 99%
“…The findings of two phase I studies of the combination of docetaxel and cisplatin have been published. 19,20 However, their results are not applicable to cancer patients in Japan, because there is a distinct difference in the approved doses for single-agent use of docetaxel between that in Western countries (75-100 mg/m 2 ) and that in Japan (60 mg/m 2 ). [12][13][14][15][16][17] It was therefore essential to conduct a phase I study of the combination of these drugs in Japan.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, it is occasionally observed after highly aggressive chemotherapies against solid tumors [5]. Two cases of NE or NEC have been reported after the appliance of pemetrexed in the treatment of NSCLC [4,10]. To date, only one case of fatal NEC has been reported after chemotherapy for MPM [11].…”
Section: Discussionmentioning
confidence: 99%